2015
DOI: 10.6018/analesps.31.1.167241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of assisted training with neurofeedback on EEG measures, executive function and mood in a healthy sample. [Efectos del entrenam. asistido con neurofeedback sobre el EEG, los procesos de función ejecutiva y el afecto en una muestra de pobl. normal]

Abstract: Efectos del entrenamiento asistido con neurofeedback sobre el EEG, los procesos de función ejecutiva y el estado de ánimo en una muestra de población normal Milena Vasquez, Marien Gadea, Evelio Garijo, Marta Aliño y Alicia Salvador Departamento de Psicobiologia, Facultat de Psicologia, Universitat de ValènciaResumen: El entrenamiento en neurofeedback (NF) consiste en enseñar a los individuos a modificar, regular y potenciar su patrón de actividad cerebral. El objetivo de nuestra investigación fue evaluar el ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Studies that focus on young adults as a target group administrate protocols to alter or improve various psychological processes such as working memory (Astrand, 2018;Sherwood et al, 2016), working and episodic memory (Hsueh et al, 2016;Wei et al, 2017), mood (Gruzelier, 2014a;Herwig et al, 2019), attention (Gadea et al, 2016;Jurewicz et al, 2018;Sherwood et al, 2019), mental imagery ability (Toppi et al, 2014), attention alongside mind-wandering (Gonçalves et al, 2018), attention and motor system excitability (Studer et al, 2014), auditory evoked potentials (Rieger et al, 2018), and executive functions (Enriquez-Geppert et al, 2017;Hosseini et al, 2016;Vasquez et al, 2015).…”
Section: Field Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that focus on young adults as a target group administrate protocols to alter or improve various psychological processes such as working memory (Astrand, 2018;Sherwood et al, 2016), working and episodic memory (Hsueh et al, 2016;Wei et al, 2017), mood (Gruzelier, 2014a;Herwig et al, 2019), attention (Gadea et al, 2016;Jurewicz et al, 2018;Sherwood et al, 2019), mental imagery ability (Toppi et al, 2014), attention alongside mind-wandering (Gonçalves et al, 2018), attention and motor system excitability (Studer et al, 2014), auditory evoked potentials (Rieger et al, 2018), and executive functions (Enriquez-Geppert et al, 2017;Hosseini et al, 2016;Vasquez et al, 2015).…”
Section: Field Overviewmentioning
confidence: 99%
“…Only two empirical studies focused on investigating the effects of neurofeedback on executive functions (Hosseini et al, 2016;Vasquez et al, 2015). While Vasquez et al (2015) focused on the increase of beta (13-21 Hz) with inhibition of theta (4-7 Hz) band using one active electrode (Cz), Hosseini et al (2016) used Near-infrared spectroscopy (NIRS) to offer neurofeedback through measurements on changes in oxygenated hemoglobin in the prefrontal cortex using a 52channel EEG. Although different approaches were administrated, both studies presented significant improvements in executive functions.…”
Section: Executive Functionsmentioning
confidence: 99%
“…In fact, the success of Enriquez-Geppert, Huster, Figge and collaborators (2014) and Wang and Hsieh (2013) might indicate that the amount of training needs to be high, at least more than 180 min, to induce significant NFT effects. Furthermore, our descriptive review pointed to the scarce efficacy of theta single-session NFT protocols (i.e., Gonçalves et al, 2018;Vasquez et al, 2015). Overall, our analysis suggested that NFT on frontal-midline theta measured from Fz (and neighboring electrodes) has been shown more frequently as effective in modulating this band and behavior than NFT protocols that did not include frontal-midline region electrodes.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 82%
“…A distinction should be drawn as two specific subprotocols were included, namely, low beta NFT targeting a frequency range from 14 to 18 Hz and SMR (12-15 Hz), none of which was successful. Except for two single-session studies (Gonçalves et al, 2018;Vasquez et al, 2015), NFT duration was generally high (120-528 min) and this does not seem to be the cause. In contrast, we observed frequent methodological drawbacks, especially in the "not successful" studies.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 91%
See 1 more Smart Citation